2018
DOI: 10.17584/rcch.2018v12i2.7226
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation protocol for the wild Brazilian greenberry (Rubus erythroclados)

Abstract: This study presents the first micropropagation protocol for greenberry (Rubus erythroclados), a wild Brazilian species with edible green fruits. In the in vitro multiplication stage, three concentrations of benzyladenine (BA) were tested (0, 5 and 10 μM), combined with three concentrations of indolebutyric acid (IBA) (0, 3 and 6 μM) in two subsequent subcultures. In the rooting stage, in and ex vitro rooting were compared after pulse treatment of the microcutting for 10 seconds in IBA (0, 2.46, 4.92 and 7.38 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Currently, this species is described as an unconventional food plant due to its green fruits with high sugar levels and pleasant taste [3,4]. R. erythroclados has the potential to be among the main small fruits grown in Brazil together with blackberry and raspberry because of the quality of its fruits [5].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, this species is described as an unconventional food plant due to its green fruits with high sugar levels and pleasant taste [3,4]. R. erythroclados has the potential to be among the main small fruits grown in Brazil together with blackberry and raspberry because of the quality of its fruits [5].…”
Section: Introductionmentioning
confidence: 99%
“…are commonly known as whiteberries or greenberries, alluding to the color of the fruits that remain green even when ripe (Bueno, 2015). The fruits have high levels of sugar and a pleasant peculiar flavor, which gives market potential compared to other small fruits (Bueno, Biasi, & Tofanelli, 2018). Information about the ethno-knowledge of these species in the Santa Catarina South Plateau indicates that although they are much appreciated for their sweet taste and were less acidity than blackberries their consumption is made only in fresh fruits mode, when the fruits are found at random, without the habit of collection for processing (Couto Waltrich, Boff & Boff, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For greenberries, vegetative propagation studies indicate that multiplication via cuttings is inefficient, whereas in vitro cultivation requires adjustments and further studies (Bueno, 2015). The in vitro propagation of R. erythroclados was evaluated by Bueno et al (2018) who found low rooting rates and paralyzed studies, which highlights the necessity of retake work on development of specific protocols for these species. Micropropagation can provide better seedling uniformity and vigor, increased mass production and better health (Dutra, et al, 2010), in addition to allowing molecular biology work to conserve plant genetic resources (Bakhtiar, Mirjalili, & Sonboli, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Asimismo, los reguladores de crecimiento empleados para inducir una respuesta morfogénica en explantes de Rubus incluye a citocininas y auxinas (Bueno et al, 2018), citocininas y giberelinas (Cancino-Escalante et al, 2015;Millones, 2018;Pérez-Martínez Castañeda-Garzón, 2016). Además, para la elongación de los brotes de R. ideaus ha sido empleado brasinolido, hormona vegetal de tipo esteroidal (Robres-Torres et al, 2015).…”
Section: Introductionunclassified